Formatting print layouts with CSS3 - Götz, Christin; Nikolaus, Ulrich (Journal of Print and Media Technology Research, 2023)
Cascading Style Sheets (CSS) have already been the de facto standard for the visual representation of digital content for some time now. However, advanced functions intended for the formatting of print layouts have been included only recently. With CSS level 3, which is still under development, several new features have been added to the standard, such as, for example, the definition of marginalia, footnotes, running heads or the support for advanced micro-typographic settings like OpenType features. In theory, these new features could be the key to a significant simplification of cross-media publishing, based only on the use of XML or (X)HTML and CSS3. In this paper, the current status of implementation of CSS3 features for the formatting of XML-based print layouts is discussed and its current support by rendering engines analyzed. The results suggest that CSS3 can be used at present for the formatting of simply structured content, but not for visually or semantically complex print layouts.